Analisa Beban Kerja Mental Pada Karyawan Divisi Produksi Cv Sarana Sejahtera Tehnik - Ilham Prasetyo Nugroho; Vita Efelina (Jurnal Ilmiah Wahana Pendidikan, 2022)
Analysis of mental workload on employees of the production division Cv technical welfare facilities In the current era of globalization, especially in the industrial sector, every company is required to provide complete production of goods, facilities and infrastructure and can later be used by consumers comfortably and safely, as well as workers qualified and professional to achieve the effectiveness, efficiency and productivity of a company. The purpose of this study is related to work activities and the time needed by employees of CV Sarana Sejahtera Tehnik and to find out the mental workload/pressure on these employees. In this study, the method used is the National Aeronautics and Space Administration Task Load Index (NASA-TLX) with a questionnaire. From the results of data processing, it can be concluded that the employees/operators of Cv Sarana Sejahtera Tehnik have a relatively high mental workload. The first worker is Catur Pras Dewo, male gender, the position of operator in the production division with a mental workload of 97.3%. Then for the second worker on behalf of Sanusi, male gender, the position of operator in the production division with a mental workload of 86.67%.